The dynamics of organ donation in Palestine: legal, religious, and socioeconomic perspectives in a complex political and economic landscape - Hattab, Muayad K.; Rahhal, Belal M.; Mahamid, Fayez; Adas, Noor O.; Dawas, Rana; Jaradat, Nidal; Al Zabadi, Hamzeh; Ali, Iyad; Kielani, Jamal; Musleh, Ali; Khaled, Ghassan (Frontiers in Public Health, 2025)
BackgroundOrgan donation in Palestine is influenced by a unique blend of legal, religious, and socioeconomic factors compounded by the region’s political and economic instability. Despite the increasing need for organ transplantation, public hesitation and misconceptions hinder participation. This study aimed to explore these dynamics, identify barriers, and provide insights into improving organ donation practices in Palestine.MethodsA quantitative survey was conducted among 639 Palestinian adults residing on the West Bank. The survey assessed participants’ attitudes, awareness, and perceptions of organ donation across three domains: religious/psychological, medical, and legal. The data were analyzed using chi-square tests and three-way ANOVA to explore differences in attitudes based on demographic factors such as sex, academic level, and place of residence.ResultsThe study revealed significant variability in public attitudes toward organ donation, with 43.4% willing to donate organs after death but 30% still opposed. Religious and psychological awareness significantly influenced participants’ attitudes, with 40.35% agreeing that organ donation aligns with their beliefs. Medical awareness was higher, with 48.8% feeling informed about the process. Legal awareness was moderate, with 44.85% understanding of the legal framework. The analysis showed no significant demographic differences in attitudes toward organ donation.ConclusionPublic awareness, religious beliefs, and socioeconomic conditions play crucial roles in shaping organ donation attitudes in Palestine. This study highlights the need for targeted educational campaigns that integrate religious perspectives and raise awareness about the legal and medical aspects of organ donation. Strengthening legal frameworks and healthcare infrastructure will be key to improving organ donation rates and ensuring ethical practices in the region.